Nineteenth century English oratorio festivals - Andrews, C (2011)
Oratorio festivals were an important cultural feature of nineteenth-century English society. These massive musical events lasted for three or four days and some involved up to 4,000 musicians and 83,000 in the audience. This dissertation advances the hypothesis that the oratorio festivals, and the grand new buildings in which they were staged, coalesced to create a musical monumentalism in a society steeped in the (mainly Protestant) Christian sentiments of the day. In particular, the dissertation contends that a central premise of nineteenth-century musical thought was that the musical value of a performance was directly in proportion to the size of the performing forces and the audience. A framework devised mainly from Stephen Little's definition of monumental art (2004) is used as a critical tool to examine from a new perspective aspects of nineteenth-century oratorios such as 'physical scale', 'breadth of subject matter', and 'ambition to be of lasting significance'. Furthermore, this dissertation argues that a complex ideology of an English musical monumentalism underpinned the concatenation of circumstances that allowed oratorio festivals to flourish at this time. The spectacle of the Crystal Palace in London and the Great Handel Triennial Festivals it housed are contrasted with the provincial festivals, such as those of Bristol, Manchester, Liverpool, Birmingham, and Leeds. The analyses of the latter rely on substantial original material uncovered from rich primary source documents about the provincial oratorio festivals and the buildings in which they were held. Musical scores themselves, including some of Sir Michael Costa's orchestral manuscripts, are also examined as monuments. A comprehensive study of these festivals is well overdue and this study will aim to understand why these events grew to such a mammoth size at this time.